Taboo and Euphemisms in the Lexems Expressing Customs and Traditions - Ismoilova Nodirabegim Usmonjon qizi (Zien Journals, 2022)
The article analyzes the lexemes of tradition from a linguistic point of view. The method of component analysis aims to determine the origin, meaning, etymological synonyms and secondary motivation.
Keywords: taboo; euphemisms; custom lexemes; tradition